2013
DOI: 10.1038/bjc.2013.507
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous hormone use, reproductive history and risk of adult myeloid leukaemia

Abstract: Background:A hormonal aetiology is one explanation for the lower incidence of myeloid leukaemia in women compared with men.Methods:In this population-based case–control study, we evaluated associations between exogenous hormone use and reproductive history and myeloid leukaemia, overall and by disease subtype.Results:We observed a suggestive association between oral contraceptive use and acute myeloid leukaemia (odds ratio=0.55, 95% confidence interval=0.32–0.96). Hormone replacement therapy and reproductive f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…In contrast to our findings for MPN, Poynter, et al (17) found no association between the use of HT and risk of myeloid leukemia (AML or CML). Similarly, in the IWHS cohort, Ross, et al (18) found no associations between ever use of HT and risk of AML.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings for MPN, Poynter, et al (17) found no association between the use of HT and risk of myeloid leukemia (AML or CML). Similarly, in the IWHS cohort, Ross, et al (18) found no associations between ever use of HT and risk of AML.…”
Section: Discussioncontrasting
confidence: 99%
“…We are not aware of other studies in myeloid malignancies that have specifically analyzed quartiles of ovulatory years; other investigators have reported associations of age at menarche, parity, and OC use with mixed results. Poynter, et al (17) found no association between age at menarche, parity, OC use or menopausal status with risk of CML, however, they found a reduced risk of AML among those that were premenopausal at diagnosis and OC use for >5 years (OR=0.55; 95% CI 0.32–0.96). Conversely, Traversa, et al (29) reported a non-significant increased risk of acute leukemia among their cohort of women who had filled at least one OC prescription.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the role of estrogen in hematopoietic diseases has long been controversial. Traversa G et al [ 24 ] have found that oral contraceptives are a potential risk factor for AML, but Poynter et al [ 25 ] have analyzed the clinical data and found that the risk of postmenopausal AML declines in people who take oral contraceptives for more than five years. The reasons for these inconsistent research results may be associated with the region and age distribution of the population.…”
Section: Discussionmentioning
confidence: 99%
“…Although the findings were based on only a few rat carcinogens this result may indicate a potentially important mechanism for cancer development in this organ, possibly also for humans. Although there are articles reporting on potential links between hormonally active substances and cancer of the hematopoietic system in humans ( Traversa et al, 1998 ; Poynter et al, 2013 ; Leal et al, 2016 ), the aetiologies of this cancer type are still unclear ( Laurier et al, 2014 ). More research is required to support these findings and it would, e.g., be of interest to evaluate the structures of the chemicals in more details and investigate potential links with hormonal receptors.…”
Section: Discussionmentioning
confidence: 99%